2021
DOI: 10.1007/s10973-021-11054-0
|View full text |Cite
|
Sign up to set email alerts
|

Amorphous alloys and differential scanning calorimetry (DSC)

Abstract: A remarkable number of scientific papers are available in the literature about the bulk amorphous alloys and metallic glasses. Today, DSC is an essential tool for amorphous alloys research and development, and of course for quality assurance. In many cases, users seek to examine the determination of only one or two properties, although much more information can be obtained from the measurements. The research involved structural relaxation, Curie temperature, glass temperature, crystallization, phase separation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(6 citation statements)
references
References 100 publications
(105 reference statements)
1
5
0
Order By: Relevance
“…The Differential Scanning Calorimetric (DSC) technique is well established to be one of the powerful tools to distinguish the crystalline and the amorphous states of the solid‐state samples [ 56,57 ] such that the required DSC study is performed to reaffirm the degree of crystalline nature of the NSH sample with respect to their planes. Note that dehydration of water molecules is not dealt with for the NSH sample as more focus is given to the melting point of the DSC measurements that were performed using a DSC60 plus in the temperature range of 35 to 300 °C at a scanning rate of 5 °C min −1 in the nitrogen gas atmosphere.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Differential Scanning Calorimetric (DSC) technique is well established to be one of the powerful tools to distinguish the crystalline and the amorphous states of the solid‐state samples [ 56,57 ] such that the required DSC study is performed to reaffirm the degree of crystalline nature of the NSH sample with respect to their planes. Note that dehydration of water molecules is not dealt with for the NSH sample as more focus is given to the melting point of the DSC measurements that were performed using a DSC60 plus in the temperature range of 35 to 300 °C at a scanning rate of 5 °C min −1 in the nitrogen gas atmosphere.…”
Section: Resultsmentioning
confidence: 99%
“…[48][49][50][51][52][53][54][55] More interestingly, in the case of the (4211) plane, the lattice Raman mode is shifted from 201 to 192 cm −1 while here also one higher wavenumber lattice Raman mode has disappeared and such kind of significant changes in the Raman lattice modes clearly show the formation of local lattice disorder in the case of the (4211) plane. [48][49][50][51][52][53][54][55] The Differential Scanning Calorimetric (DSC) technique is well established to be one of the powerful tools to distinguish the crystalline and the amorphous states of the solid-state samples [56,57] such that the required DSC study is performed to reaffirm the degree of crystalline nature of the NSH sample with respect to their planes. Note that dehydration of water molecules is not dealt with for the NSH sample as more focus is given to the melting point of the DSC measurements that were performed using a DSC60 plus in the temperature range of 35 to 300 °C at a scanning rate of 5 °C min −1 in the nitrogen gas atmosphere.…”
Section: Lattice Raman Modesmentioning
confidence: 99%
“…The differential scanning calorimetry (DSC) technique is a wellestablished powerful tool that is used to distinguish the crystallographic order and disorder state of solid-state samples [63][64][65][66][67] such that the required DSC study has been performed to reaffirm the observed shock-wave-induced order to disorder phase transition of the title sample and the recorded DSC thermograms for the control, first, and second shocked samples are displayed in Figure 10. As seen in Figure 10, the control ammonium sulfate has two endothermic peaks at 318 and 436 °C and the observed values are found to be very consistent with the previous reports.…”
Section: Ultraviolet Diffused Reflectance Spectroscopic Analysismentioning
confidence: 99%
“…The crystallization process in metallic glass can be analyzed using, among others, a differential scanning calorimeter (DSC) [7]. Next, models popular in the literature, such as Johnson-Mehl-Avrami [8,9] and Kissinger [10], are used for the interpretation of energy values from DSC experiments.…”
Section: Introductionmentioning
confidence: 99%
“…Next, models popular in the literature, such as Johnson-Mehl-Avrami [8,9] and Kissinger [10], are used for the interpretation of energy values from DSC experiments. Therefore, it is possible to calculate the kinetic parameters and draw conclusions about the stability of glass, as well as the rate and nature of crystallization (the nucleation and growth of crystals at different stages of the process) [7,11]. The improper use of a model or rate constant in experimental data can, however, lead to physically meaningless or, worse still, misleading results.…”
Section: Introductionmentioning
confidence: 99%